Investment Policy Analysis Between Generation Z and Millennial Generation - Fadali Rahman; Aditya Iskandar Syah; aisyah, Aisyah Safitri; ayu, Ayu Maulidia; subhan, subhan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study aims to analyze and This study uses a quantitative approach with a comparative associative survey method and involves 100 respondents (50 Gen Z and 50 Millennials) who are domiciled in Indonesia and have investment experience, with a purposive sampling technique . comparing investment policies between Generation Z and Millennials in Indonesia. These two demographic groups are "Digital Natives" who are familiar with the development of information technology and investment applications. Primary data were collected through an online questionnaire and analyzed using Multiple Linear Regression and Independent Sample t-test with the help of the SPSS program.The results of the regression analysis show that financial literacy (X1), investment knowledge (X2), and investment risk (X3) simultaneously and partially have a significant effect on investment policy (Y) in both generations. The coefficient of determination (R2) value of 0.652 indicates that 65.2% of the variation in investment policy can be explained by these three variables.The results of the comparative test ( Independent Sample t-test ) with a Sig. (2-tailed) value = 0.018 (<0.05) indicate a significant difference in investment policies between Generation Z and the Millennial Generation.Generation Z (born 1996–2010) tends to be more daring in taking risks and is quicker in adopting digital investment technologies such as applications (Bibit, Bareksa, Ajaib, IPOT), and chooses instruments with medium to high risk (stocks and digital assets).The Millennial generation (born 1981–1995) exhibits more conservative behavior , oriented towards the security and stability of assets , with a preference for relatively low-risk instruments such as mixed mutual funds, deposits, and blue-chip stocks.These findings reinforce Behavioral Finance theory , emphasizing the importance of individual understanding, experience, and risk perception in investment decision-making. The research's implications suggest the need for the government/OJK to expand digital financial literacy programs tailored to each generation, as well as the development of educational and secure features by securities firms.